The ideal theory in Plato’s Philosophy and it’s relevance to man and the universe - ALbogami, Nadha Mutlaq (Arab Journal for Sciences and Research Publishing, 2023)
The study aimed to shed light on the ideal theory in Plato’s philosophy and the major issues addressed by this philosophy, as well as its successors who carried its torch after Plato. The study aimed to uncover the foundations and principles upon which ideal philosophy was based. The researcher utilized a historical methodology at times and a descriptive methodology at other times, depending on the different parts of the research. The study revealed that Plato sought, through his theory of Ideas, to find the true abode of the soul. According to Plato, truth lies in Ideas, which are the source of the similarity of things and the eternal and immutable patterns underlying natural phenomena. The study concluded that human nature consists of the mind (soul) and matter (body), and in Plato’s view, the mind represents the soul. The soul, in his perspective, is immortal and immaterial, while the human body is born, grows, and withers. The important issues addressed by the ideal theory include the mind, society, values, truth, good and evil, knowledge, and the world.
Keywords: Plato; Ideal Theory; Universe; Philosophy